Toward high degree flexible routing in collision-free FMSs through automated guided vehicles' dynamic strategy: A simulation metamodel. (January 2020) - Mohammadi, Ehsan Karimi; Shirazi, Babak
Abstract: The present study proposes a simulation-based model of high degree flexible routing to prevent collisions and deadlocks in flexible manufacturing systems (FMSs). High degree flexible routing concurrently involves classical routing strategies (specifies the destination and static/dynamic routing between origin and destination) with routing flexibility (considers alternatives to select as destination). A new approach named Tandem-Queue-Link with a look-ahead (TQL-A) is proposed in which the look-ahead mechanism supports deadlock prevention. The TQL-A performs a collision-free status for automated guided vehicles (AGVs) routing with flexible dynamic strategy. The main contribution of the present study is to implement the routing flexible levels (RFLs) by dynamic flexible routing (DFR) as a high degree flexible routing strategy. The most efficient parameters of this highly complex FMS are designed using a multi-objective nonlinear programming model extracted from simulation metamodels based on different hypotheses. Results support some of the considered hypotheses and show the complicated relationship between different values of FMS design parameters and different levels of routing flexibility. Metamodel validity through a typical case study defines that the higher values of velocity and acceleration/deceleration can compensate the level of routing flexibility but other parameters that are influenced by the active parameter (i.e. those related to loading/unloading time) have not any sensible influence on the output. Highlights: Synthesize high degree flexible routing to prevent collisions and deadlocks in FMSs through AGVs. Concurrent handling of the routing flexible levels (RFLs) and dynamic flexible routing (DFR) using a proposed method. A new Tandem-Queue-Link with a look-ahead (TQL-A) strategy to prevent collisions via simulation-metamodel. Compensating the level of flexible routing by the higher values of velocity and acceleration/deceleration. Graphical abstract: